1996
DOI: 10.1021/ja954075s
|View full text |Cite
|
Sign up to set email alerts
|

Mass Dependence of Uranium Isotope Effects in the U(IV)−U(VI) Exchange Reaction

Abstract: Isotope separation of 233U by anion exchange chromatography based on the U(IV)−U(VI) exchange is studied. After long-distance migration, 233U enrichment is observed at the rear band boundary. To examine the isotope effects of 233U, 234U, and 238U, three-isotope plots of local enrichment factors are constructed for the isotopes contained in sample fractions of the eluted uranium band. The results clearly show an anomalous mass dependence for 233U. We previously reported that the even-mass nuclides 232U, 234U, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
85
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 16 publications
6
85
0
1
Order By: Relevance
“…The anomalous 235 U-238 U isotope effect in U(IV)-U(VI) chemical exchange shown by the present authors (M. N. and Y. F.) could not be explained by the molecular vibration theory [9]. Later on, the same trend was found in the case of 233 U isotope effects [10]. It was suggested that the isotope effects in the U(IV)-U(VI) exchange system arise mainly from the interaction between the nuclei and the electrons in the isotopes.…”
Section: Introductionsupporting
confidence: 71%
“…The anomalous 235 U-238 U isotope effect in U(IV)-U(VI) chemical exchange shown by the present authors (M. N. and Y. F.) could not be explained by the molecular vibration theory [9]. Later on, the same trend was found in the case of 233 U isotope effects [10]. It was suggested that the isotope effects in the U(IV)-U(VI) exchange system arise mainly from the interaction between the nuclei and the electrons in the isotopes.…”
Section: Introductionsupporting
confidence: 71%
“…Nuclear field shifts have long been known in optical spectra of atoms and ions, but Bigeleisen (1) and Fujii and coworkers (8) were the first to recognize that the same phenomenon could lead to chemical fractionation of isotopes. They showed that uranium isotope separation via ion exchange columns (the Asahi process) tracked nuclear charge radii (or more specifically, the effective meansquare charge radius), rather than nuclear masses (1,8,9). Field shift effects are also expected to scale in proportion to the difference in electron densities inside the nucleus of the relevant atoms in the fractionating species (10).…”
mentioning
confidence: 99%
“…In 1989, one of the present authors Y. F. and co-workers reported an anomalous mass-independence in the U (IV)-U (VI) electron-exchange reaction [4]. Nomura and Y. F. et al [5] again analyzed the U (IV)-U (VI) isotope fractionation among 232 U, 233 U, 234 U, 235 U, 236 U, and 238 U. Figure 1 shows the correlation between mass difference of isotopes and the slope of three-isotope plot, θ, which is the value to be proportional to isotope fractionation coefficients.…”
Section: Introductionmentioning
confidence: 63%
“…Typical examples are the uranium isotope fractionations in oxidation-reduction equilibrium states, such as the U (III)-U (IV) [2,3] and U (IV)-U (VI) [4,5] exchange systems. These systems show large isotope effects that are inexplicable by the standard theory.…”
Section: Introductionmentioning
confidence: 99%